Synthesis and new skin-relevant properties of the salicylic acid ester of bakuchiol. Issue 5 (4th March 2023) - Quijas, Geovani; Haliński, Łukasz P.; Gobis, Katarzyna; Bojanowski, Ryszard; Bojanowski, Krzysztof
Abstract: Bakusylan (bakuchiol salicylate) is a bipartite compound obtained by merging two skin-active entities with complementary bioactivities—bakuchiol and salicylic acid—for the purpose of generating a new class of functional retinoids with enhanced skin benefits. Here, we describe its preparation process and report that pure bakusylan exhibits potential for an improved permeation through the stratum corneum, enhances type IV collagen gene expression in organotypic skin substitutes containing both epidermal and dermal layers, and upregulates this protein in adult human dermal fibroblast cultures. The mechanism of action underlying these effects appears to involve the components of the IP3K/Akt signaling pathway selectively implicated in the maintenance of skin integrity, further underlying the suitability of this ester for skin care applications requiring enhanced cutaneous permeation targeting the dermal-epidermal junction. Graphical Abstract: UF0001